Community Service regarding the importance of giving birth in health facilities in Cijakan Village, Bojong District, Pandeglang Regency, Banten in 2023 - Mulianti, Amanda Eka Mulianti; Shinta Novelia; Putri, Amelia; Faradilla Puteri Rochayu; Ami Rachyani; Juninda Putri; Laila Hanif Assyuri; Rahayu Indah Lestari; Ricke Muriadi (Rajaki of Tulip Medika Publisher, 2024)
Background: Health problems receive serious attention from various elements of society. One way to overcome health problems in society is to carry out community service. Community service is an activity that aims to help the community overcome the problems they face by actively participating in the health development process and increasing community empowerment. Objective: Carry out community service by carrying out activities ranging from assessment to intervention and evaluation of field activities. So that it can build public knowledge so they can live healthier, safer and more prosperous lives. Method: Community Midwifery Practice has been carried out by National University Midwife Professional Education Students in Cijakan Village, Bojong District, Padeglang Regency, Banten. with stages: Orientation, secondary data collection, Village Community Deliberation (MMD), Action Planning (POA), intervention activities in the form of counseling on